2015
DOI: 10.5194/gmdd-8-3653-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ECCO version 4: an integrated framework for non-linear inverse modeling and global ocean state estimation

Abstract: Abstract. This paper presents the ECCO v4 non-linear inverse modeling framework and its baseline solution for the evolving ocean state over the period 1992–2011. Both components are publicly available and highly integrated with the MITgcm. They are both subjected to regular, automated regression tests. The modeling framework includes sets of global conformal grids, a global model setup, implementations of model-data constraints and adjustable control parameters, an interface to algorithmic differentiation, as … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
349
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(376 citation statements)
references
References 126 publications
(122 reference statements)
3
349
0
2
Order By: Relevance
“…Previous publications have demonstrated that the estimates fit altimetry , SST (Buckley et al 2014), subsurface hydrography data (Forget et al 2015a), and the Atlantic meridional overturning circulation (Wunsch and Heimbach 2013b) at or close to the specified noise level. Many quantities (e.g., isopycnal mixing) for which no corresponding observations are available have been analyzed in some detail and found to be at least physically plausible (Forget et al 2015b).…”
Section: Data and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous publications have demonstrated that the estimates fit altimetry , SST (Buckley et al 2014), subsurface hydrography data (Forget et al 2015a), and the Atlantic meridional overturning circulation (Wunsch and Heimbach 2013b) at or close to the specified noise level. Many quantities (e.g., isopycnal mixing) for which no corresponding observations are available have been analyzed in some detail and found to be at least physically plausible (Forget et al 2015b).…”
Section: Data and Processingmentioning
confidence: 99%
“…In this study, we use the ECCO v4r1 estimate (Forget et al 2015a) and analyze the net air-sea heat flux Q net and the ocean vertical heat flux H y . The ECCO v4r1 estimate covers the period 1992-2011, when altimetry measurements of high precision, quasi-global coverage of ocean in situ measurements, mainly Argo temperature and salinity profiles, and the WOCE hydrographic program and the follow-on hydrography, are available.…”
Section: Data and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the atmosphere is often divided between the long-term impact of buoyancy forcing due to air-sea fluxes of heat and freshwater and the action of winds on the sea surface (Polo et al 2014;Forget and Ponte 2015). The ocean circulation can adjust to the latter on short time scales (hours to months) through barotropic dynamics (Willebrand et al 1980;Andres et al 2011Andres et al , 2012) and on longer time scales (years to decades) through various baroclinic modes (Anderson and Gill 1975;Williams et al 2014;Forget and Ponte 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Progress in this area is attributable primarily to the Global Ocean Data Assimilation Experiment project, which, crucially, supports near-real-time collection, processing, and management of oceanographic data [6] [7]. In addition, several state-of-the-art community ocean models, which can be coupled with data assimilation schemes, have been developed as open-source code (e.g., ROMS [8] and ECCO [9]) and have contributed to making ocean nowcasting and forecasting relatively easy. Consequently, physical oceanographic studies have made rapid progress in the areas of ocean dynamics and predictability.…”
Section: Introductionmentioning
confidence: 99%